Nutritional requirements and bioavailability of different sources of zinc and manganese for broilers - Carvalho, Bruno Reis (2017)
Two experiments were conducted to evaluate the zinc (Zn) and manganese (Mn) requirements for broilers from organic and inorganic sources, as well as the relative bioavailability of these sources. In each trial 510 male Cobb broilers were used. The animals were raised according to strain guidelines from 1 to 7 days receiving 50% supplementation from the tested mineral in a diet with reduced content of traceminerals. At 8 days 10 animals were slaughtered to verify the mineral deposition at the beginning of the experiment. The other animals were weighed and randomly distributed in plastic cages in 10 treatments with 10 replicates of 5 animals each. The treatments consisted of 5 levels of traceminerals tested (0, 19, 38, 57 and 76 mg/kg of Zn in the first experiment and 0, 25, 50, 75 and 100 mg/kg of Mn in the second), provided in an organic or inorganic supplement, where the other minerals were supplied to meet the requirement. The diets used were semi purified to reduce the content of traceminerals to low levels. At 13 days, trays covered with plastic were installed for excreta collection. At 16 days in the Zn experiment and 17 days in the Mn experiment the animals and feds were weighed to determine the final weight, weight gain, feed intake and feed to gain ratio. At 17 days in the Zn experiment and 18 days in the Mn experiment a bird in each cage were slaughtered for determination of minerals in the liver. The results for the Zn experiment indicate that the requirement for higher performance is 70 mg Zn/kg of weight gain (WG) for inorganic supplementation, which can be reduced to 63 mg Zn/kg of WG in organic mineral supplementation. Higher Zn retention was observed when 62 mg/kg of Zn was supplied in inorganic form or 79 mg/kg of organic Zn. Interactions in Mn and iron retention have been observed in supply of inorganic Zn as well as in the deposition of Mn and iron in the liver when organic sources are provided. The relative bioavailability of the organic Zn was estimated to be 125% of the inorganic Zn. For Mn, the requirement determined based on the performance parameters is 166 mg Mn/kg of WG for the Mn supply in the inorganic form and 95mg Mn/kg WG in the organic form. The highest retention of Mn was obtained with the supply of 68.8 and 84.6 mg/kg of Mn in the diet for organic and inorganic sources, with a relative bioavailability estimated at 100%.